ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH MELAKUKAN AKUISISI DAN MERGER PADA PERUSAHAAN NON KEUANGAN - Geovana Rizky Firdaus; Siti Ruhana Dara (LPMP Imperium, 2020)
This study aims to analyze Comparative Analysis Before and After Merger and Acquisition of Financial Performance of Companies Listed on the Stock Exchange for the 2013-2017 period. The population used is a non-financial company registered on the IDX that carries out merger and acquisition activities for the period 2013-2017. Samples are determined by purposive sampling technique and obtained 9 companies. Types of quantitative research. The data analysis method used is the normality test, and hypothesis testing using the Wilcoxon signed-rank test non-parametric test paired sample t-test. Wilcoxon signed-rank test for CR, TATO, ROA and NPM, DER testing, paired sample t-test for DR at 1 and 4 years after mergers and acquisitions has Asymp.Sig (2-tailed) value is greater than the significance value set α = 0.05 (> 0.05). CR experiences significant differences, TATO has no difference 1 before and 4 years after, ROA and NPM get results that do not have significant differences, DER and DR did not experience significant results on financial performance. So that the company's financial performance remains a fairly stable situation.